Synthetic cannabinoid for the treatment of severe chronic noncancer pain in children and adolescents. Issue 1 (31st December 2022) - Sun, Naiyi; Cunha, Natasha; Amar, Shawnee; Brown, Stephen
ABSTRACT: Background: The prevalence of chronic pain in children and adolescents is high. In some patients, it can be severe and refractory to conventional treatment options. There is increasing interest in the use of cannabinoids for therapeutic purposes in children and adolescents. Nabilone, a synthetic cannabinoid, is approved in Canada for the treatment of nausea and vomiting associated with chemotherapy. It can also be used off label for treatment of chronic pain. Aims: This study aims to characterize the use of nabilone for severe chronic pain in a pediatric population. Methods: This is a retrospective cohort study of patients 18 years or younger who were prescribed nabilone for chronic pain in a tertiary multidisciplinary pediatric chronic pain clinic between July 1, 2013, and June 30, 2017. Results: During the 4-year study period, we screened the charts of 507 patients and identified a total of 28 patients (5.5%) who were treated with nabilone as part of their chronic pain treatment. Common indications for nabilone treatment include mixed neuropathic/nociceptive pain, abdominal pain, neuropathic pain, and spasticity. In all patients, nabilone was prescribed as an adjunctive treatment. Seven patients (25%) reported a slight improvement in pain symptoms. Side effects were reported by 21.4% of patients. The most common reported side effects were sedation and cognitive slowing. Conclusions: Adjunctive treatment with nabilone may improve pain symptoms in a subset of pediatric chronic pain patients. Further research investigating the long-term safety and efficacy of nabilone in the treatment of chronic pain in children is needed.